Towards Systematic Tuning of Standard-Compliant, Multi-Area Agc Systems - Chavez-Orostica, H; Avila-Araya, T (Institute of Electrical and Electronics Engineers Inc., 2017)
Due to different technical-economical reasons, power systems tend to interconnect each other. The resulting system after the interconnection could be reorganized into two or more control areas in terms of secondary frequency control; if this is the case, the resulting control areas may require new automatic generation control (AGC) parameters to maintain compliance with performance standards. In addition, the continuous integration of variable distributed generation into the network tend to increase the need for secondary control, thus systematic AGC definition procedures are required. This work proposes a heuristic method to tune the AGC parameters for interconnected systems subject to secondary frequency control performance standard compliance. An illustrative example in a hypothetical interconnection of two identical ERCOT equivalents is presented to validate results. © 2017 IEEE.